Influence of long-range transported Asian dust on cirrus cloud formation over central Pacific - He Yun; Shen Huijia; Yin Zhenping (E3S Web of Conferences)
Cirrus clouds play a vital role in regulating the global radiative balance and climate, with their net radiative forcing determined by microphysical properties, which are strongly related to the ice-nucleating mechanisms, i.e., heterogeneous or homogeneous nucleation. However, there are lack of direct observational cases regarding the influence of long-range transport of Asian dust on primary ice formation in cirrus over the Pacific. Here we report on two such dust-cirrus interaction cases over the central Pacific with the combined observations of space-borne Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) and Cloud Profiling Radar (CPR). Both cases show good agreement (within an order of magnitude) of in-cloud ICNC and nearby dust-related INP concentration (INPC) values, indicating that dust-induced heterogeneous nucleation is dominated in ice formation. This study shows that the natural supply of effective INPs to the upper troposphere can modulate the microphysical properties of cirrus clouds by acting as INPs and further influence on global climate. This information is useful for parameterizing ice formation in climate models.